The Effect of Palm Oil Mill Effluent and Cow Manure on the Growth and Yield of Bok Choy Plant (Brassica Rapa L.) - Pratama, Boby Erdi; Hafifah, Hafifah; Nazaruddin, M; Nasruddin, Nasruddin; Faisal, Faisal (Yayasan Pertanian Tropika Indonesia (YPTI), 2022)
In Indonesia, bok choy (Brassica rapa L.) is a popular vegetable whose leaves are used as food ingredients in fresh or processed ways. The treatments to increase the production of bok choy are the application of Palm Oil Mill Effluent (POME) and cow manure fertilizer. POME contains macro and micronutrients such as C, N, P, K, Ca, and Mg that can optimize plant height, number of leaves, and plant production. This research aims to measure the effect of POME and cow manure fertilizer as well as the interaction of these fertilizers on the growth, production, and quality of bok choy. The research was arranged in a randomized block design with two factors. The first factor was Palm Oil Mill Effluent (POME) (L) consisted of L0 (0 ml), L1 (150 ml/polybag), L2 (250 ml/polybag). The second factor was cow manure fertilizer (K) consisting of K0 (0 ml) K1 (100 g/polybag) K2 (200 g/polybag). The results showed that the application of POME affects plant height at 28 DAP, the number of leaves at 28 DAP, and leaf chlorophyll content in bok choy plants. The best treatment is L1 (150 ml/polybag of POME) which increases the growth and yield of bok choy plants. Applying cow manure affects the plant height at 28 DAP, number of leaves at 28 DAP, plant fresh weight, root fresh weight, crown fresh weight, dry weight, and harvest index of bok choy plants. The best treatment was found in K1 (100 grams/polybag of cow manure) which increased the growth and yield of bok choy plants. There is an interaction between the treatment of POME and cow manure on the plant height at 21 DAP, number of leaves at 28 DAP, plant fresh weight, root fresh weight, crown fresh weight, plant dry weight, and harvest index. The best treatment is found in the interaction of L1K1 (100 ml/polybag of POME + 100 g/polybag of cow manure) which increased the growth and yield of bok choy plants.